2019
DOI: 10.1177/0361198119833974
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Incentive for Slow Steaming in Chinese Sulfur Emission Control Areas

Abstract: The increasing concerns caused by marine environmental issues have aroused attention from international agencies and regional governments about the regulation of the amount of ship emissions. There are various measures and regulations to control shipping emissions, among which emission control areas (ECAs) have been recognized as an effective tool to restrict shipping emissions along coastlines. Realizing the serious damage caused by shipping emissions, the Chinese Ministry of Transport announced the establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…They found that slow steaming within SECAs slightly decreases operators' total costs and increases CO 2 emissions. Fan and Huang [11] discussed the slow steaming inside the Chinese SECA, which demonstrated the effectiveness of the Chinese sulfur limit. To summarize, slow steaming is an economic method to save energy costs due to the big price spread between low-and high-sulfur bunkers, hence slow steaming is necessary to be considered in the fuel-switching option.…”
Section: Emission Abatement Methods From Shipsmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that slow steaming within SECAs slightly decreases operators' total costs and increases CO 2 emissions. Fan and Huang [11] discussed the slow steaming inside the Chinese SECA, which demonstrated the effectiveness of the Chinese sulfur limit. To summarize, slow steaming is an economic method to save energy costs due to the big price spread between low-and high-sulfur bunkers, hence slow steaming is necessary to be considered in the fuel-switching option.…”
Section: Emission Abatement Methods From Shipsmentioning
confidence: 99%
“…In addition to the above-mentioned studies, some researchers have analyzed the effects of slow steaming on emission abatement [11,34,36,37]. Doudnikoff and Lacoste [14] examined the effects of speed reduction inside SECAs by solving a cost-minimizing model with heuristic approach.…”
Section: Emission Abatement Methods From Shipsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ECA regulations require the operator to switch to expensive low-sulfur fuels, and thus have great side effects on many aspects of shipping operations; namely, speed and route [22][23][24].…”
Section: The Eca Regulations and Their Impactsmentioning
confidence: 99%